Analisis Nilai-Nilai Moral pada Novel Cerita Cinta Enrico Karya Ayu Utami - Natalia Mercyana; Katharina Woli Namang (Asosiasi Periset Bahasa Sastra Indonesia, 2025)
This study aims to know the form and form of moral values contained in the novel of the love of ayu utami in her daily life. the method used is qualitative. The object of research in the novel love story of entrico, this study will focus on analyzing moral values in the novel. Data collection techniques are reading and notes. The reading technique is carried out by reading the story novel of enriek repeatedly and as a whole to clearly understand the contents of the story novel Enico by Utami's love story. Then the next step is to look for moral values in the novel langakah the next is to record the moral values contained in the novel Enico love story. This recording technique is to determine and analyze moral values in the novel of Enico's love story. The results of the study showed that the novel of the love story of Enico by ayu Utami includes, moral, religious, and education values. The moral value that we learn in Enrico love story is, as humans should have a clear life goal so that in the future we get life and kebahagin. The religious value is seen from his parents who are one religious Muslim and others are Christians, then Enrico himself does not choose a religion and belief. The value of education, namely Enrico, continues his education at a university in one of the universities in Bandung which is known as ITB, majoring in mining.